Rancangan Perbaikan Kualitas Pelayanan Jasa Dengan Metode Servqual, Importance Performance Analysis, Dan Quality Function Deployment Pada Plasa Telkom Cabang Dinoyo Surabaya - Angga Dharmawan; Febriana Wurjaningrum (Universitas Airlangga, 2014)
Measuring the level of customer satisfaction is one of the important factors to overcome the competition is rapidly increased. By knowing the level of customer satisfaction from services provided, the company could undertake the mapping of improved service quality. By using the integration method servqual, IPA, and QFD, the service provider is able to determine the level of customer satisfaction and straightly can make improvements of service with low levels of satisfaction. This research was conducted at Plasa TELKOM Dinoyo Surabaya’s branch. From the questionnaires showed that all the attributes of service quality in the questionnaire have a negative gap value. In IPA method showed 6 attributes with high importance and low value the fact. The quality improvement to be done such as improving the application of SOP, increasing the number of officers, officials periodically evaluate, reward the best employees every month, the maximization of information technology systems, and implementing 4S culture are really needed.